EXPERIENCE REPORT ON THE ACTIVITIES DEVELOPED DURING THE PEDAGOGICAL RESIDENCE PROGRAM WITH EMPHASIS ON THE PROJECT DEVELOPED DURING THIS COURSE - Aparecida Barbosa de Sousa, Maria (Revista Gênero e Interdisciplinaridade, 2023)
The present work aimed to describe the experiences acquired during the Pedagogical Residency Program, highlighting the actions carried out in the development of the project. The methodology is based on a qualitative, descriptive and exploratory approach, using writing as the articulating axis for the production of this research. In summary, the results show us how demanding the moment of the pandemic and remote teaching was, since the teacher had to adapt to deal with the difficulties that the covid-19 pandemic taught. Considering the difficulties encountered in distance learning during this atypical period, the use of technological resources was of paramount importance and became the only alternative for us to continue the training process, the regency during the Pedagogical Residency also took place virtually, and a one of the main problems we observed in this was the evasion of students in the virtual classroom, in view of this scenario, we created a project entitled: the reflection of the pandemic in the socio-emotional and school demotivation: a look of students and teachers in the face of the adversities of remote teaching, soon , it was possible to observe the real reason for evasion during remote classes, thinking about it, we decided to carry out activities about the motivation of these students, with that, we held lectures with themes directed to these issues present in remote teaching. Through the facts mentioned above, the importance of these meetings is perceived, since necessary topics were worked with students in the face of the pandemic context, since this project was aimed at mitigating the impacts caused in the educational environment.